Immutable mobiles: Assessing and contesting sustainability in European quinoa farming - Volpini, Giulia; Legun, Katharine; Vicol, Mark; Andreotti, Federico (The International Journal of Sociology of Agriculture and Food, 2025)
Sustainability assessment methodologies such as Life Cycle Assessment (LCA) are becoming increasingly prevalent in the evaluation of agri-food value-chains. Proponents of such assessment methodologies argue that they offer a factual and robust measure of the sustainability impacts of food production. Yet, assessment methodologies have attracted criticism for portraying a partial representation of the phenomenon. For example, existing LCA models tend to operationalize simplified and generalizable ideals of sustainability. These operationalizations mobilize understandings of sustainability that may clash with the grounded, experientially-based understandings of local actors such as farmers. Using a theory of translation and the concept of immutable mobiles, we consider how LCA seeks to stabilize a definition of sustainability by delineating what aspects of agriculture may be considered relevant for sustainability and what is irrelevant, what is made visible in sustainability discourse, and what can be ignored. We then apply our analysis to a case study of quinoa farming in Europe. We compare what quinoa farmers identify as central to sustainability to what is included in dominant LCA methodologies to highlight what is excluded from LCAs: bodies, place, and qualitative aspects of the farm. In describing what is excluded, we consider how farmers are disempowered through definitions of sustainability evolved through new assessment tools, and consider how these elements of the farm become a moot point for sustainable assessment and instead are central to political contestation.   Finally, the paper argues for the transformation of power relations in the sustainability sector, which tend to isolate farmers, through the construction of new relationships between farmers and the research sector, as well as the valorization of farmers' knowledge in the definition of sustainable agriculture being advanced in policy.